Moxifloxacin and ciprofloxacin induces S-phase arrest and augments apoptotic effects of cisplatin in human pancreatic cancer cells via ERK activation - Yadav, Vikas (BMC Cancer, 2015)
BACKGROUND: Pancreatic cancer, one of the most dreadful gastrointestinal tract malignancies, with the current chemotherapeutic drugs has posed a major impediment owing to poor prognosis and chemo-resistance thereby suggesting critical need for additional drugs as therapeutics in combating the situation. Fluoroquinolones have shown promising and significant anti-tumor effects on several carcinoma cell lines. METHODS: Previously, we reported growth inhibitory effects of fourth generation fluoroquinolone Gatifloxacin, while in the current study we have investigated the anti-proliferative and apoptosis-inducing mechanism of older generation fluoroquinolones Moxifloxacin and Ciprofloxacin on the pancreatic cancer cell-lines MIA PaCa-2 and Panc-1. Cytotoxicity was measured by MTT assay. Apoptosis induction was evaluated using annexin assay, cell cycle assay and activation of caspase-3, 8, 9 were measured by western blotting and enzyme activity assay. RESULTS: Herein, we found that both the fluoroquinolones suppressed the proliferation of pancreatic cancer cells by causing S-phase arrest and apoptosis. Blockade in S-phase of cell cycle was associated with decrease in the levels of p27, p21, CDK2, cyclin-A and cyclin-E. Herein we also observed triggering of extrinsic as well as intrinsic mitochondrial apoptotic pathway as suggested by the activation of caspase-8, 9, 3, and Bid respectively. All this was accompanied by downregulation of antiapoptotic protein Bcl-xL and upregulation of proapoptotic protein Bak. Our results strongly suggest the role of extracellular-signal-regulated kinases (ERK1/2), but not p53, p38 and c-JUN N-terminal kinase (JNK) in fluoroquinolone induced growth inhibitory effects in both the cell lines. Additionally, we also found both the fluoroquinolones to augment the apoptotic effects of broad spectrum anticancer drug Cisplatin via ERK. CONCLUSION: The fact that these fluoroquinolones synergize the effect of cisplatin opens new insight into therapeutic index in treatment of pancreatic cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1560-y) contains supplementary material, which is available to authorized users.